Stability of Bendamustine Solutions: Influence of Sodium Chloride Concentration, Temperature and Container - Vigneron Jean; D'Huart Elise; Demoré Béatrice (De Gruyter, 2018)
Bendamustine is used for the treatment of non-Hodgkin lymphoma, chronic lymphocytic leukaemia and myeloma. The stability of bendamustine is highly dependent on temperature and chloride-ion concentration. Limited stability data are available. The objective of this work was to study the stability of the bendamustine reconstituted solution at 2.5 mg/mL and the diluted solution in normal saline and 1.5 % sodium chloride to evaluate a potential increase in stability.